2008
DOI: 10.1089/aid.2007.0262
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Oxidative Phosphorylation Protein Levels in Peripheral Blood Mononuclear Cells Correlate with Levels in Subcutaneous Adipose Tissue within Samples Differing by HIV and Lipoatrophy Status

Abstract: Depletion of mitochondrial DNA (mtDNA) and mtDNA-encoded respiratory chain proteins in subcutaneous (SC) fat from patients with HIV lipoatrophy have clearly demonstrated the role of mitochondrial dysfunction in this syndrome. Research in HIV lipoatrophy, however, has been severely hampered by the lack of a suitable surrogate marker in blood or other easily obtained clinical specimens as fat biopsies are invasive and mtDNA levels in peripheral blood mononuclear cells (PBMC) do not consistently correlate with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…In this study, after a median of 7 years since the completion of doxorubicin treatment, survivors of childhood high‐risk ALL treated with doxorubicin alone had 3 times the number of mtDNA copies per cell in PBMCs in comparison with children treated with doxorubicin plus dexrazoxane, but OXPHOS enzyme activities did not differ between the groups. In addition, mtDNA copies per cell in those who received dexrazoxane were within the normal ranges observed in our previous studies (100‐350 copies per cell) …”
Section: Discussionsupporting
confidence: 85%
“…In this study, after a median of 7 years since the completion of doxorubicin treatment, survivors of childhood high‐risk ALL treated with doxorubicin alone had 3 times the number of mtDNA copies per cell in PBMCs in comparison with children treated with doxorubicin plus dexrazoxane, but OXPHOS enzyme activities did not differ between the groups. In addition, mtDNA copies per cell in those who received dexrazoxane were within the normal ranges observed in our previous studies (100‐350 copies per cell) …”
Section: Discussionsupporting
confidence: 85%
“…The extracted DNA was subjected to determination of concentration by a spectrophotometric method and securely stored at −20°C until use. Total protein was extracted from PBMCs of 3.0~5.5 × 10 6 cells according to the method described elsewhere [38]. The purified protein was undergone for estimation of concentration using BCA protein assay kit (Pierce Technology) and stored at −20°C for future application after appropriate concentration determined.…”
Section: Methodsmentioning
confidence: 99%
“…Classical studies have blamed NRTI therapies of mtDNA depletion and mitochondrial dysfunction found in adipose tissue of lipodystrophy [16][17][18][19][20][21] or nonlipodystrophy HIV patients [22][23][24][25][26]. However, the role of HIV in mitochondrial adipose tissue lesion is still a matter of doubt [10].…”
Section: Introductionmentioning
confidence: 99%